2010
DOI: 10.5120/409-606
|View full text |Cite
|
Sign up to set email alerts
|

A New Fangled Insinuation for Stress Affect Speech Classification

Abstract: Demarcation in human interaction is through two channels: one transmits explicit messages; the other transmits implicit messages about the speakers themselves knowingly or unknowingly. Both linguistics and technology have invested enormous effort in trying to understand the first (explicit) channel, but the second (implicit) is not as well understood. First, building an emotion detection system makes it possible to assess the extent to which theoretical proposals explain people's everyday competence in underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The simulation results have demonstrated that, there is an enhancement in the quality metrics of speech recognition regarding computational time, learning accuracy for a speech recognition system. Nachamai et al (2010) have discussed that demarcation in human interaction is through two channels: one transmits explicit messages; the other transmits implicit messages about the speakers themselves knowingly or unknowingly. Both linguistics and technology have invested enormous effort in trying to understand the first (explicit) channel, but the second (implicit) is not as well understood.…”
Section: Related Workmentioning
confidence: 99%
“…The simulation results have demonstrated that, there is an enhancement in the quality metrics of speech recognition regarding computational time, learning accuracy for a speech recognition system. Nachamai et al (2010) have discussed that demarcation in human interaction is through two channels: one transmits explicit messages; the other transmits implicit messages about the speakers themselves knowingly or unknowingly. Both linguistics and technology have invested enormous effort in trying to understand the first (explicit) channel, but the second (implicit) is not as well understood.…”
Section: Related Workmentioning
confidence: 99%